INSTITUTIONAL RATIONALIZATION OF MANAGEMENT FOR STABLE PROGRESS OF RURAL AREAS - Marina Sergeevna IURKOVA; Anna Alexeevna GOLUBEVA; Valentina Ivanovna TROFIMOVA; Natalia Vladimirovna PROVIDONOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was carried out to assess youths participation in cassava production under value chain development programme (VCDP) in Bida local Government Area of Niger State, Nigeria, with the specific objectives of describing the socio-economic characteristics of the VCDP participants, costs and returns, level of youths participation and factors influencing youth participation in the VCDP. A multi-stage sampling technique was used to select 100 young cassava farmers and data collected were analyzed using simple descriptive statistics and probit regression analysis. The level of profitability was measured using gross margin and net farm income analysis. The results obtained shows that farmers in the study area had low formal education and were mostly married males with an average age and household size of 32 years and six (6) persons respectively. The gross margin and net farm income were N109,050.00 and N103,450.00 per hectare, respectively. The level of youths’ participation under the VCDP was moderate and this was influenced by their age, gender, level of education, marital status, household size, farming occupation and cooperative membership. The major constraints faced by the farmers includes: poor extension agents/farmers’ ratio, inadequate capital and lack of market linkage. To this end, it was recommended that change agents should enlighten farmers on the benefit of VCDP and functional cooperative that could facilitate credit and group dynamism.